Correction: Depletion of UDP-Glucose and UDP-Galactose Using a Degron System Leads to Growth Cessation of Leishmania major. - Sebastian Damerow; Carolin Hoppe; Giulia Bandini; Patricia Zarnovican; Falk F R Buettner; Carsten G K Lüder; Michael A J Ferguson; Françoise H Routier (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004205.].